Investigating the influential factors on microbially induced calcium carbonate precipitation: effects of cell density, temperature, and calcium concentration - N. Erdmann; K. Aldabbousi; D. Strieth (Discover Applied Sciences)
Abstract This study investigates the impact of key parameters—bacterial cell density, calcium ion concentration, and ambient temperature—on the kinetics and outcomes of Microbially Induced Calcium Carbonate Precipitation (MICP) using Sporosarcina pasteurii. By extending reaction conditions to cell density up to OD600 = 30, urea and calcium concentrations up to 4.5 M, and a temperature range of 4 to 75 °C, this research provides insights into the boundaries of MICP's efficiency. Zero order reaction kinetics were determined by monitoring free NH4 + and Ca2+ during MICP through ion exchange chromatography and the resulting precipitate was characterized by Fourier-transform infrared spectroscopy and microscopical imaging. Reaction kinetics demonstrated a linear correlation between cell density and ureolysis (k urea) and calcium carbonate precipitation (k calcium,) with high densities driving rapid reaction rates. Optimal precipitation rates occurred at 45 °C, beyond which thermal deactivation of urease impeded MICP. High calcium concentrations increased calcium carbonate yield but required elevated cell densities to mitigate inhibitory effects of Ca2+. Morphological and polymorphic shifts in calcium carbonate crystals were observed, transitioning from calcite at standard conditions to vaterite and aragonite under extreme scenarios (Cell density of OD600 = 30 and 65 °C respectively). These findings underscore the multi-factorial dependencies of MICP and highlight upper boundaries of these parameters for process optimization.